Measuring structure for determining the proportionality of the sagittal cleft of the edentulous jaws - Aksyonov, D.I.; Mayboroda, Yu.N.; Aksenov, I.N. (Clinical Dentistry (Russia), 2021)
Prosthetics of patients with secondary complete loss of teeth is still one of the most difficult methods of designing artificial dentition. This is due to the lack of individual criteria for digital values that determine the parameters of the distance between the tops of the alveolar ridges of the edentulous jaws, and is due to the difficulties in measuring between the objects under study. The existing numerous technical devices for anthropometric studies on plaster models of the jaws do not allow measuring the distance between the alveolar ridges on diagnostic models with particular accuracy. Objective — to increase the efficiency of the design of artificial dentition in complete removable dentures at various levels of the degree of atrophy of the alveolar processes. Materials and methods. With the help of the designed measuring device, the existing problem has been solved, which makes it possible to measure the level of divergence of the sagittal gap between the alveolar processes of the edentulous jaws in the interframe space of the articulator after determining their central ratio. Conclusions. Based on the mathematical parameters obtained using an anthropometric device, a mathematical model has been developed, which is based on the optimal options for the placement of artificial teeth at various levels of the ratio of the tops of the alveolar ridges of the edentulous jaws.